PEMANFAATAN WHATSAPP GROUP DALAM MELATIH KEMAMPUAN MENULIS DALAM BAHASA ARAB MAHASISWA PRODI PAI - Hamidah; Salafina, Agus; Hidayah, Nur (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to describe the use of WhatsApp Groups in training PAI Study Program students’ books, their responses to the use of WhatsApp and their results. This quantitative descriptive study examined 30 students of Islamic Studies Study Program as research subjects. The data was extracted through interview, observation and documentation techniques and then analyzed in data reduction activities, data presentation and conclusion drawing. The validity of the data is required by using triangulation techniques. The results showed that WhatsApp Group was used to train students’ scriptures by communicating in writing every day about academic information and daily communication such as asking how they were doing, what to do today and at the weekend. The students’ response to this good and effective activity is that it is a challenge to continue to learn and be creative which familiarizes them with using Arabic in writing and also has an effect on other maharah’s abilities by increasing vocabulary and understanding of grammar as well as increasing insight and closeness with lecturers. . The results of student writing are generally correct and some are wrong in writing and writing, but the lecturers always correct them in every conversation, so that students’ writing skills are increasing. The implication of this research is that information and communication technology can be used to help improve students’ foreign language skills.